Insights into the Crystallisation Process from Anhydrous, Hydrated and Solvated Crystal Forms of Diatrizoic Acid. Issue 3 (4th November 2014) - Fucke, Katharina; McIntyre, Garry J.; Lemée‐Cailleau, Marie‐Hélène; Wilkinson, Clive; Edwards, Alison J.; Howard, Judith A. K.; Steed, Jonathan W.
Abstract Diatrizoic acid (DTA), a clinically used X‐ray contrast agent, crystallises in two hydrated, three anhydrous and nine solvated solid forms, all of which have been characterised by X‐ray crystallography. Single‐crystal neutron structures of DTA dihydrate and monosodium DTA tetrahydrate have been determined. All of the solid‐state structures have been analysed using partial atomic charges and hardness algorithm (PACHA) calculations. Even though in general all DTA crystal forms reveal similar intermolecular interactions, the overall crystal packing differs considerably from form to form. The water of the dihydrate is encapsulated between a pair of host molecules, which calculations reveal to be an extraordinarily stable motif. DTA presents functionalities that enable hydrogen and halogen bonding, and whilst an extended hydrogen‐bonding network is realised in all crystal forms, halogen bonding is not present in the hydrated crystal forms. This is due to the formation of a hydrogen‐bonding network based on individual enclosed water squares, which is not amenable to the concomitant formation of halogen bonds. The main interaction in the solvates involves the carboxylic acid, which corroborates the hypothesis that this strong interaction is the last one to be broken during the crystal desolvation and nucleation process.